Utilization of Literature-Based Strategies to Promote Nursing Student Success - Ziolkowski, Kimberly; Mitchell, Sabrina; Studinski, Andrew; Haupt-Harrington, Rachael L. (My University, 2018)
Nursing’s Student Success Center (SSC) is available to support nursing students academically throughout their time in the program; students self-refer or are guided by their academic advisor to access the SSC for assistance with study strategies or tutoring. An integrative literature review describes the significant impact of factors such as prerequisite course performance, hours of part-time employment, first semester GPA, and English as second language, on nursing students’ performance and attrition. A Case Management Model (CMM) has been utilized to proactively identify factors related to nursing student performance and attrition (Elder, Jacobs, and Fast, 2015). Application of this and other literature-based success strategies will be piloted and evaluated at the Marshfield-site SSC. Desired long and short-term student outcomes include improved first-time NCLEX pass rate, decreased attrition, access to resources, and student satisfaction. Strategies supporting positive student outcomes will be considered for long-term inclusion.
Color poster with text and, images.
Keywords: Nursing students; Case Management Model (CMM); Posters